Intellectual capital and forward looking information disclosures incentives and impacts on financial intermediaries and corporate performance - Noghondari, Amirhossein Taebi (2012)
With the rapidly changing economic environment, the conventional financial statements are becoming less informative about the company’s current economic position and its future prospects. The current financial reporting framework cannot incorporate and report many intangible resources and future oriented information in the current corporate financial statements. These intangibles are often knowledgebased resources that create competitive advantage and are key drivers of success of organizations in the new era. Management of many proactive organizations voluntarily disclose their intellectual resources, as well as other pertinent forward looking information, in their annual reports to facilitate investors and other stakeholders to make better informed decisions. Such disclosures can attract more financial intermediaries in financial markets as well; as the results, the companies with higher intellectual and forward looking information disclosures may experience the better performance in the financial market.Most prior studies on voluntary information disclosures mainly focus on the relationship between the extent of voluntary information disclosure and corporate characteristics and corporate governance. However, this study examines how the economic disincentive/incentives (e.g. proprietary cost, growth opportunity and existence of stock based compensation plan) may affect the extent of voluntary information disclosure of both intellectual capital and forward looking information. This study also investigates whether the extent of financial intermediary following plays a significant role in explaining the relationship between the extent of voluntary information disclosure and corporate market performance in Malaysia. The required secondary data were obtained from the corporate 2010 annual reports and the S&P Capital IQ database related to 2010. Based on all pubic listed companies in Malaysian stock market, only 198 companies have available data required for this study. Some of this data include number of financial intermediary following and data on market performance. The regression results show that a firm’s growth opportunity is positively and significantly related to the extent of voluntary information disclosure. Although, significant relationship existed between stock option compensation plan and voluntary information disclosure, as well as between proprietary cost and voluntary information disclosure, the directions of these relationships are not as hypothesised. In addition, the findings of current study provide the empirical evidence that the voluntary disclosure-performance relationship is mediated by the extent of financial intermediary following. This study enhances understanding of the rationale for corporate voluntary disclosure policies on intellectual and forward looking information. More importantly, this study shows the important role that financial intermediaries plays in disseminating of such relevant information in the capital market that subsequently influences corporate market performance, the results also help to explain the mixed findings regarding the effects of voluntary disclosures on corporate performance. The findings would be of interests to practitioners such as investors and corporate managers as well as academic researchers.